Review on bio-inspired synthesis of silver nanoparticles: their antimicrobial efficacy and toxicity - Prasad, S.R.; Teli, S.B.; Ghosh, J.; Prasad, N.R.; Shaikh, V. S.; Nazeruddin, G.M.; Al-Sehemi, Abdullah G. Al; Patel, Imran; Shaikh, Y.I. (Engineered Science, 2021)
Silver nanoparticles are one of the most studied compounds in materials science due to their antimicrobial efficacies and, for instance, in photocatalysis, dye-sensitised solar cells, and biomedical devices. However, conventional methods of synthesis of silver nanoparticles (AgNPs) require hazardous and costly chemicals, and a large amount of energy is expended. In this review, efforts have been made to target where eco-friendly synthetic techniques are being conducted using various plant extract to develop nanoparticles in inexpensive, easily scaled up, and environmentally benign. These findings are stimulated intense research activities that focused on synthesis, modification, properties, and applications of these ecofriendly nanoparticles. This review covers all these aspects, such as the biological routes for the synthesis of nanoparticles employed to synthesis the nano-silver using algae, bacteria, plants, fungi, etc. Also, the chemical positions and possible traditional uses of the plants are enlisted.